Financial Inclusion Knowledge, Spending Behavior, and Ease of Use on Interest in Using the DANA Application - Suseno, Bambang (Maneggio, 2024)
This study aims to examine how financial inclusion knowledge, spending behavior, and ease of use influence students' interest in using the DANA application. Financial inclusion knowledge is considered important as it provides an understanding of digital financial products and services, while spending behavior reflects how individuals manage their expenses and make financial decisions. Furthermore, the application's ease of use is a key factor that can influence users' interest in adopting financial technology like DANA. This research employs a quantitative approach using a survey method. Data from 100 students in Deli Sumatera University's management study program was collected using a questionnaire and analyzed using multiple linear regression. The research results show that knowledge of financial inclusion, spending behavior, and ease of use have a positive and significant impact on the interest in using the DANA application. Among these three variables, knowledge of financial inclusion has the most dominant influence on the interest in usage. The more students know about financial inclusion, the more they want to use DANA. In addition, planned spending behavior and the ease of using the DANA application also play a significant role in encouraging interest in using the app. Based on these findings, this research contributes to understanding the factors that influence interest in using digital financial applications and supports the enhancement of financial inclusion among students